Audiovisual modeling: An efficient, time-saving, radiation-specified method of reducing dental anxiety in children undergoing panoramic radiographic imaging and IOPA radiographic imaging - Rupali V Mhaske; Lata M Kale; Vishwas D Kadam; Aishwarya M Kale; Vijaya M Ingle; Snehal S Vispute (Wolters Kluwer Medknow Publications, 2019)
Background: Children undergoing panoramic radiographic imaging (PRI) and intraoral periapical (IOPA) radiographic imaging show anxiety due to the presence of a revolving PRI machine and IOPA X-ray unit and a different environment which can pose behavioral concerns. Staying still for 15-20 s is not possible for young children. This could lead to distortions and require repetitions, leading to more radiation exposure. Aim: The aim of the study was to reduce the dental anxiety and reduce the increased radiation exposure and saving time in PRI and IOPA radiographic imaging by audiovisual modeling. Methodology: Forty children age 2-12 years indicated for PRI and IOPA radiographic imaging were subjected and observed before and after audiovisual modeling. The patients were modeled by audiovisual modeling before imaging in the oral radiology department. The anxious and disruptive behavior was assessed using the anxious and disruptive behavior code by a single blinded observer. Statistical Analysis Used: Statistical Software SPSS 13.0. Results: There was significant difference in the occurrence of body movement and complaining and restraint before and after audiovisual modeling in the same patients. There were statistically significant differences in the overall events before and after audiovisual modeling. Conclusion: The basic behavior management technique and use of audiovisual modeling can reduce the anxiety and disruptive behavior in children undergoing PRI and IOPA radiographic imaging and also reduces increased radiation exposure, saving time for the process thus reducing the cost of repeated imaging.